Cloning of the GH gene from the beluga sturgeon (Huso huso) into a lentivial & none viral constructs and it’s expression in HEK cell lines - Mashjoor, S.; Zolgharnain, H.; Gardaneh, M.; Salari Aliabadi, M.A.; Qasemi, A.; Azimi, Z. (2014)
Caviar-producing fish with their economically valuable product are important in fisheries. The cDNA growth hormone (GH) of Beluga sturgeon (Huso huso) was constructed using total RNA from pituitary glands. To construct the recombinant and active lentiviruses carring GH gene, this DNA sequence was inserted into the cloning vector pTZ57R/T and subsequently cutted from pTZ57R/T by endonuclease enzyme and incorporated into lentivirus vector pNL-EGFP/CMV-WPRE on upstream of an IRES cassette. We also insert a reporter EGFP gene downstream of IRES so transfection and transduction steps can be traced. Using this vector plus virus packaging and envelope vectors, HEK293T cells was co-transfected by DNA-Lipofectamine complexes method. Cell supernatant full of virions was collected 48 hours later and concentrated using Amicon columns to obtain a high-titer virus stock. Nearly 1/5 of this stock was applied to a new batch of cultured HEK-293T. After 72h expression of EGFP gene was detected and the cells was collected for further analysis. Total RNA of these transduced cells was extracted and GH mRNA expression was revealed by RT-PCR. Results showed that, lentiviral vectors (LV) as a gene transfer system provide efficient delivery, integration and long-term expression by establishing a stable provirus in target cells and could be important tool in aquaculture and fisheries biotechnology research to increase the growth rate of farmed fish by transferring growth hormone (GH) transgenes into fish.